Essentials of pharmacology - Nawaz, Shah (Paramount Books Limited, 2013)
Questions and answers in pharmacology and theraputics for all time busy dental, medical and pharmacology students takes a cursory view of pharmacology. Identifying important topics, it minimuzes the time to read while maximizing the time to learn at the same time. Common questions based od each topic emeging throughout the book facilitate memorization, and spell out essential concepts. Its question-and-answer format fosters quick learning. This up-to-date edition incorporates the recents developments in the field of pharmacology therapeutics.